Alternative food shoppers and the 'quantity dilemma': A study on the determinants of their purchases at alternative markets - Clara Cicatiello (Agricultural and Food Economics, 2020)
Despite the increasing interest around alternative food networks and their huge growth in the last decades, they are still considered a complementary source of provision by most customers. Alternative food shoppers are faced with a "quantity dilemma", i.e., choosing how much food they want to buy through these channels. This decision affects the importance of alternative food networks in the market and the extent to which they may contribute to the improvement of the food systems' overall sustainability. Basing on a survey involving 1200 food shoppers interviewed at alternative markets in Italy, this paper studies the factors explaining the quantity of food that customers choose to buy there, with respect to the quantity they purchase through conventional channels. Results show that their motivations to buy at alternative markets are crucial to increase the share of food provisions attained through these channels, especially when quality and environmental motivations are concerned. Another key factor is the type of alternative market where consumers are used to shop at, with box schemes being more likely to represent a main source of food provision for their customers than farmers' markets and farm shops. A strong effect is played by customers' loyalty to alternative markets, showing that establishing a long-term relation with producers participating at alternative markets increases the probability of buying more food through these channels. These findings disclose a potential in terms of upscaling of alternative food networks, linked to the identification of the consumers segments that are more likely to use these channels as a main source of food provision, and to the types of business models that can more likely increase the quantity of food purchased.
Keywords: 330; Alternative food networks; Local food systems; Short food supply chain; Local food; Farmers' market; Food purchase; Consumer behavior; Logistic regression